2017
DOI: 10.1038/srep42555
|View full text |Cite
|
Sign up to set email alerts
|

A novel orally bioavailable compound KPT-9274 inhibits PAK4, and blocks triple negative breast cancer tumor growth

Abstract: Breast cancer is a heterogeneous disease consisting of several subtypes. Among these subtypes, triple negative breast cancer is particularly difficult to treat. This is due to a lack of understanding of the mechanisms behind the disease, and consequently a lack of druggable targets. PAK4 plays critical roles in cell survival, proliferation, and morphology. PAK4 protein levels are high in breast cancer cells and breast tumors, and the gene is often amplified in basal like breast cancers, which are frequently tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 60 publications
4
46
0
Order By: Relevance
“…Thus, confirmation of an anti-cystic effect in several separate models of ADPKD, in vitro, ex vivo , and in vivo , strengthens our conclusions regarding the potential utility of this inhibitor for treatment of the human disease. Research from our laboratory showed that when KPT-9274 was orally administered to a 786-O (VHL-mut) human RCC xenograft model, there was dose-dependent inhibition of tumor growth with minimal toxicity 9 , data which is in line with several other recent publications from other institutions when KPT-9274 was administered both intravenously 18 and orally 16,17 , the latter up to 42 days 17 . Currently, KPT-9274 is being evaluated in a Phase 1 human clinical trial in patients with advanced solid malignancies or NHL (NCT02702492), thus there have been toxicity studies performed in a variety of animal models that allowed initiation of this clinical study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, confirmation of an anti-cystic effect in several separate models of ADPKD, in vitro, ex vivo , and in vivo , strengthens our conclusions regarding the potential utility of this inhibitor for treatment of the human disease. Research from our laboratory showed that when KPT-9274 was orally administered to a 786-O (VHL-mut) human RCC xenograft model, there was dose-dependent inhibition of tumor growth with minimal toxicity 9 , data which is in line with several other recent publications from other institutions when KPT-9274 was administered both intravenously 18 and orally 16,17 , the latter up to 42 days 17 . Currently, KPT-9274 is being evaluated in a Phase 1 human clinical trial in patients with advanced solid malignancies or NHL (NCT02702492), thus there have been toxicity studies performed in a variety of animal models that allowed initiation of this clinical study.…”
Section: Discussionsupporting
confidence: 88%
“…It can be seen that total-PAK4 and to a lesser extent total-β-catenin, were decreased in the kidneys from treated animals (Fig. 5b), consistent with target engagement of KPT-9274 17 . In the Pkd1 flox/flox :Pkhd1-Cre mice, KPT-9274 treatment resulted in significantly decreased cyst growth, kidney size, and BUN when compared to vehicle treated controls (Fig.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Given our biochemical findings, the structural features of KPT-9274, and reports suggesting NAMPT as a target of KPT-9274 in other systems, [41][42][43][44] we tested whether KPT-9274 acts through a pathway involving NAMPT inhibition in AML cells. Protein expression of NAMPT was variable in a panel of malignant myeloid cell lines and primary AML cells, as shown in Figure 3A.…”
Section: Nampt As the Primary Target Of Kpt-9274 In Aml-treated Cellsmentioning
confidence: 99%
“…PAK4 is involved in a variety of cytoskeletal regulation such as promoting filopodia formation, dissolution of stress fibers, controlling actin polymerization and depolymerization as well as focal adhesion turnover [19][20][21][22][23][24][25] . Consistently, PAK4 overexpression is correlated with poor patient outcome in breast cancer patients, and its overexpression in breast cancer cell lines was shown to increase cell survival, anchorage-independent growth, cell migration and invasion [26][27][28][29][30] . PAK4 also plays an essential role during embryonic development, as complete depletion of PAK4 in mice caused embryonic lethality with severe defects in the heart, brain, and vasculature of the animals; however, its role in mammary gland development has not been investigated [31][32][33] .…”
Section: Introductionmentioning
confidence: 76%